Synthesis and Applications of Conductive Polyaniline Rice Husk Ash Silica Nanocomposites: A Comprehensive Review - Mezan, Salim Oudah; Hello, Kasim Mohammed; Jabbar, Abdullah Hasan; Abed, Anwar Khairi; Hamzah, Maytham Qabel; Tuama, Alaa Nihad; Roslan, M.S.; Agam, Mohd Arif (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
Recently, the development of Nanotechnology, Nanoscience and Nanomaterial have received more attention following its optical, mechanical, electrical and chemical properties. Nanostructures have a prominent place in Nanotechnology since more space can be used in different applications. In the past decades, a class of conductive polymers became famous because of their mechanical and electrical properties. Polyaniline is a conductive polymer popularly known as an environmentally stable and highly adjustable polymer given in an application form of powder, membranes or loose fibres. Low-cost polyolefin and large-scale production are widely used in broad applications. Rice Husk Ash (RHA) is the by-product of the rice mill industry considered as waste material. Many types of research focused on RHA target the highly contained silicate to be converted to silica after Rice Husk (RH) pyrolysis undertaken in a furnace with a temperature of (800oC). The sol-gel technique offered a simple route in producing silica from RHA, where 3- (chloropropyl) triethoxyscilane (CPTES) is used to convert the RHA into high-quality silica. Polyaniline/Rice Husk Ash Silica Nanocomposite (PANI/RHACCl (SiO2)NCs) are prepared via chemical oxidative polymerization and can be used in various applications such as supercapacitors, pseudocapacitors, coatings, metal absorption, chemicals, encapsulation of light-emitting organs, proton exchange membrane, diffusion membrane, devices Sensor, Nanoelectronic flexible devices, as well as drug delivery. Results have shown that PANI encapsulates SiO2 Nanoparticles with a very powerful impact on Nanocomposite morphology.